Evaluation Survey of Physical Education Learning in The Merdeka Belajar Curriculum - syahri, Muhammad; Kari, Rangga (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
This study aims to evaluate the development of the Physical Education, Sports, and Health (PJOK) learning process in the implementation of the Independent Learning curriculum. The research was conducted at Teladan Sei Rampah High School in the academic year 2022/2023. The success of the implementation of this new curriculum is measured through surveys and direct observations of students. Participants in this study were high school students at Teladan Sei Rampah who were involved in the PJOK learning process using the Independent Learning curriculum. The research design adopts a quantitative approach with data collection using questionnaires and observations. The instruments used include structured questionnaires and observation checklists to provide a comprehensive overview of the implementation of learning. The collected data were analyzed using the SPSS statistical application. The results of the data analysis include an evaluation of the effectiveness of the Independent Learning curriculum in improving the PJOK learning process. The findings of this research will provide better insights into the extent to which the curriculum meets the educational goals and needs of students. Based on the results of the analysis, the study concludes on the success or shortcomings of the Independent Learning curriculum in enhancing the PJOK learning process at Teladan Sei Rampah High School. This conclusion contributes significantly to a better understanding of the implementation of the new curriculum in the context of sports education at the high school level. Furthermore, this research provides a foundation for future studies related to the development of curricula and more effective learning strategies in an evolving educational context. Keywords: Evaluation, Merdeka belajar Curriculum, Senior High School